2013
DOI: 10.1103/physrevlett.110.210403
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement Swapping between Photons that have Never Coexisted

Abstract: The role of the timing and order of quantum measurements is not just a fundamental question of quantum mechanics, but also a puzzling one. Any part of a quantum system that has finished evolving can be measured immediately or saved for later, without affecting the final results, regardless of the continued evolution of the rest of the system. In addition, the nonlocality of quantum mechanics, as manifested by entanglement, does not apply only to particles with spacelike separation, but also to particles with t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
106
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(118 citation statements)
references
References 39 publications
(29 reference statements)
11
106
0
Order By: Relevance
“…The earlier experiments were performed by Freedman and Clauser (1972), and Aspect, Grangier and Roger (1982). Recently, some independent experiments have proved that two particles were always entangled after they had been measured (Ma, Zotter, Kofler, Ursin, Jennewein, Brukner, & Zeilinger, 2012), and demonstrated that the nonlocality of quantum mechanics does not apply only to particles with spacelike separation, but also to particles with temporal separation (Megidish, Halevy, Shacham, Dvir, Dovrat, & Eisenberg, 2013); Yin (2013) claimed that the speed of Einstein's "spooky action at a distance" is at least 10,000 times fast than light. These studies confirm that, although a loophole or two are still outstanding, the original formulation of quantum mechanics is indeed correct.…”
Section: Empirical Intermediary Among Many-worldsmentioning
confidence: 99%
“…The earlier experiments were performed by Freedman and Clauser (1972), and Aspect, Grangier and Roger (1982). Recently, some independent experiments have proved that two particles were always entangled after they had been measured (Ma, Zotter, Kofler, Ursin, Jennewein, Brukner, & Zeilinger, 2012), and demonstrated that the nonlocality of quantum mechanics does not apply only to particles with spacelike separation, but also to particles with temporal separation (Megidish, Halevy, Shacham, Dvir, Dovrat, & Eisenberg, 2013); Yin (2013) claimed that the speed of Einstein's "spooky action at a distance" is at least 10,000 times fast than light. These studies confirm that, although a loophole or two are still outstanding, the original formulation of quantum mechanics is indeed correct.…”
Section: Empirical Intermediary Among Many-worldsmentioning
confidence: 99%
“…A PBS completes the error correction protocol. The multiple phase accumulation part is implemented by a 31.5 m long delay line, projecting photons from different pulses [38]. Two 22.5 o HWPs are placed before the projecting PBS to avoid the collapse of the state by the measurement of the first photon.…”
Section: Fig 1 (Color Online)mentioning
confidence: 99%
“…More experimental details and a discussion on the entanglement swapping between delayed photons can be found in Ref. [38]. …”
Section: Fig 1 (Color Online)mentioning
confidence: 99%
“…27 This claim is not correct because: a) "can affect" is a causation statement, but correlation is not causation; and b) instantaneity is mistakenly read into these experiments as if the quantum entanglement was only between simultaneous states, but physicists have recently shown that quantum correlation is possible between photon pairs that never coexisted (Megidish et al, 2013).…”
Section: On Time With Time In Physics: a Personal Perspectivementioning
confidence: 99%